Green treasures: Investigating the biodiversity potential of equine yards through the presence and quality of landscape features in the Netherlands. - Inga A Wolframm; Lara Heric; Andrew M Allen (PLoS ONE)
At a time of mounting ecological crises and biodiversity loss, there is an urgent need for nature-based solutions. Equestrian properties cover a considerable proportion of the European rural and peri-urban landscape and provide much potential for integrating ecosystem services, such as the inclusion of small landscape features. The aim of this study was to investigate the presence and quality of landscape features (LF) to help determine how the equine sector can contribute to the agro-ecological transition. Using a citizen science approach, 87 commercial and 420 private yard owners reported the type, frequency and geometric dimension of LFs and additional biodiversity enhancing features. A hierarchical multivariate regression was used to determine how equine property characteristics explain variation in the Percentage Property Coverage (PPC) of LFs. The model explained 47% of the variation of PPC. The variables that explained significant variation in PPC included Yard size, Number of LFs, Tree rows, Fruit orchard, Wild hedges, Flowering strips, Buffer strips, Embankments and Cluttered corners. Commercial yards are significantly larger with significantly more horses and on average only 9% (±13.87%) of the property was covered by LFs whilst private yards had significantly more coverage of LFs with on average 12% (±14.77%). These findings highlight the substantial yet untapped potential of equine yards in fostering biodiversity, suggesting that the equine sector could play an important role in the agro-ecological transition. To encourage more biodiverse-inclusive yard designs, tailored strategies should consider the diverse factors influencing equine yard design, including existing knowledge, client demands, financial considerations, and equine health and welfare.